The Role of Muslim Women in Family Education - Henri Shalahuddin; Achmad Tryandi Qois (al-Afkar, Journal For Islamic Studies, 2024)
Education is very important in the continuity of human life. Education functions as a foundation in organizing human life in a more moral, ethical manner and also in order to give birth to a good civilization, so to form good and quality morals and ethics a quality educational pattern is needed. The need for quality educational patterns cannot be separated from the role of educators as spearheads that determine the journey of students. So it is appropriate for every Muslim woman to receive a high education to be able to become a strong foundation for her family and even for the surrounding community. And every Muslim must be smart in preparing the family he will build, because what will be built is a society that will give birth to civilization